The Curiosity Rover's Exploration of Glen Torridon, Gale Crater, Mars: An Overview of the Campaign and Scientific Results. Issue 1 (30th December 2022) - Bennett, Kristen A.; Fox, Valerie K.; Bryk, Alex; Dietrich, William; Fedo, Christopher; Edgar, Lauren; Thorpe, Michael T.; Williams, Amy J.; Wong, Gregory M.; Dehouck, Erwin; McAdam, Amy; Sutter, Brad; et al.
Abstract: The Mars Science Laboratory rover, Curiosity, explored the clay mineral‐bearing Glen Torridon region for 1 Martian year between January 2019 and January 2021, including a short campaign onto the Greenheugh pediment. The Glen Torridon campaign sought to characterize the geology of the area, seek evidence of habitable environments, and document the onset of a potentially global climatic transition during the Hesperian era. Curiosity roved 5 km in total throughout Glen Torridon, from the Vera Rubin ridge to the northern margin of the Greenheugh pediment. Curiosity acquired samples from 11 drill holes during this campaign and conducted the first Martian thermochemolytic‐based organics detection experiment with the Sample Analysis at Mars instrument suite. The lowest elevations within Glen Torridon represent a continuation of lacustrine Murray formation deposits, but overlying widespread cross bedded sandstones indicate an interval of more energetic fluvial environments and prompted the definition of a new stratigraphic formation in the Mount Sharp group called the Carolyn Shoemaker formation. Glen Torridon hosts abundant phyllosilicates yet remains compositionally and mineralogically comparable to the rest of the Mount Sharp group. Glen Torridon samples have a great diversity and abundance of sulfur‐bearing organic molecules, which are consistent with the presence of ancient refractory organic matter. The Glen Torridon region experienced heterogeneous diagenesis, with the most striking alteration occurring just below the Siccar Point unconformity at the Greenheugh pediment. Results from the pediment campaign show that the capping sandstone formed within the Stimson Hesperian aeolian sand sea that experienced seasonal variations in wind direction. Plain Language Summary: The Mars Science Laboratory rover, Curiosity, explored a valley called Glen Torridon on the lower slopes of a sedimentary mountain within Gale crater, Mars, between January 2019 and January 2021. The rocks within this shallow valley are part of a sequence of rock layers whose mineral composition could imply a transition from a wetter to drier environment more than 3 billion years ago. This paper reports on the exploration campaign designed to understand the local geology, document evidence of past climate change, and investigate if the ancient environments may have been amenable to biological activity. Curiosity found that many rocks were deposited in the bottom of a lake, but also that river deposits occur frequently in this area, suggesting that the environmental conditions changed through time. Curiosity observed evidence for multiple cycles of water interacting with the sediments that chemically changed the elemental and mineralogical compositions of the rock layers. Curiosity collected 11 drill holes over the course of the campaign and found abundant clay minerals, as predicted, as well as a wide variety of organic molecules, suggesting that the ancient environment contained many of the necessary conditions to support life. Key Points: Sedimentary facies within Glen Torridon record a transition from low‐energy lacustrine mudstones to higher‐energy fluvial sandstones Glen Torridon hosts the highest clay mineral abundances observed thus far by Mars Science Laboratory (MSL) while remaining in family with the Mount Sharp group Glen Torridon drill samples contain the greatest diversity of organic compounds yet detected by the MSL mission